ANALISIS SENTIMEN OPINI PUBLIK MENGENAI SARANA DAN TRANSPORTASI MUDIK TAHUN 2019 PADA TWITTER MENGGUNAKAN ALGORITMA NAÏVE BAYES, NEURAL NETWORK, KNN DAN SVM - Melisa Winda Pertiwi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
Various moments are immortalized in social networking, one of them Twitter. Twitter is one of the social media that allows users to interact, share information, or even to express feelings and opinions as well as in expressing opinions about